Advances in industry 4.0 : concepts and applications - Niranjanamurthy, M. (De Gruyter series on smart computing applications ;, 2022)
This book presents the emerging technologies of Industry 4.0. It describes the growing trend towards automation and data exchange in the manufacturing industry, with a focus on the internet of things (IoT), the industrial internet of things (IIoT), cyberphysical systems (CPS), smart factories, cloud computing, cognitive computing, and artificial intelligence.